ANALYSIS OF PAPER ABSORPTION FROM DRIED LEAVES AS POTENTIAL OF FUTURE ORGANIC SANITARY PADS - Handika Dany Rahmayanti; Septia Ardiani; Nurul Akmalia (Jurnal Ilmiah Publipreneur, 2019)
The use of waste, as well as unused goods, becomes something that has a sales value which is very necessary to preserve the environment. One example is the use of dry leaf waste which can be transformed into goods of economic value to the people who use them. The transformation of dry waste into pulp is one of the efforts that can be made to overcome the waste problem. The pulp from the dried leaf waste can then be turned into a paper which can then be used as an alternative to sanitary pads.